Digitalizing MSME Financial Recording in Medan: The Development and Implementation of a User-Centered POS System - Barus, Okky Putra; Maulana, Ade; Sinaga, Triandes (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community engagement project aimed to address operational challenges faced by Micro, Small, and Medium Enterprises (MSMEs) through an integrated Point of Sales (POS) system. A case study at Akane Beauty Studio and Salon used a User-Centered Design (UCD) and Rapid Application Development (RAD) approach, managed under the PMBOK framework. The implementation yielded a significant impact on operational efficiency, notably reducing transaction time from over one minute to under one minute. A comparison of the workflow also showed improvement, with a manual process that previously took four minutes now being completed in two minutes. User Acceptance Testing (UAT) confirmed the system was fully functional and easy to use. This project demonstrates that a user-centric digital solution can tangibly improve the efficiency, data accuracy, and business sustainability of MSMEs.